Ankyloglossia - from histogenesis, and parafunctional implications to legal aspects: a bibliographic review - Samuel Saidymon Soares Alves; Luisa Laura Lima Reis; Patrícia Capuço Oliveira; Débora Andalécio Ferreira; Lia Dietrich; Aletheia Moraes Rocha (Associação Brasileira de Odontologia, 2018)
Objective: to address the consequences of ankyloglossia when there is no early intervention, in addition to the expected legal implications. Material and Methods: this study checked the databases of PubMed, Bireme, Google Scholar, Scielo, Lilacs and Medline. Out of 30 articles found, nine were discarded because they did not identify with the objectives. Results: ankyloglossia is a congenital disorder of the lingual frenulum that limits the elevation and protrusion of the tongue due to its short extension and has repercussion throughout the stomatognathic system. It is verified in the literature that the tongue is fully formed in the second month of gestation and that the frenulum is formed after apoptosis of the lingual brake cells and reabsorption of the developing skeletal muscle. Therefore, ankyloglossia is classified in five degrees, according to its mobility, and in four types, according to its thickness and elasticity. The Neonatal Tongue Screening Test is applied in compliance of a law and not performing this test can lead to anatomical and functional consequences for the mother and the baby. The recommended treatment is the frenectomy, although frenotomy and Z-Plasty can be used. Conclusion: the conclusion is that the health professionals should not neglect the test, to avoid worsening this condition.